Bolivia and Its Transformations in the Light of "Seven Erroneous Theses about Latin America". (March 2018) - Canedo Vásquez, Gabriela
Bolivia has become a plurinational state, and as such it seeks to dismantle the deeply ingrained internal colonialism that runs through the state and the society. Thus it recognizes self-determination by indigenous people, autonomous territories, plural economy and justice, communal democracy, and suma qamaña (living well) and identifies the indigenous as the main actors in the transformation process, sidelining both the working and the middle classes. Some of the contradictions at its core include views of development that range from extractivism to environmentalism and living well. The government claims to be oriented toward communitarian socialism, but developmentalism will entail the destruction of indigenous modes of survival that are considered culturally rich but backward from a Western perspective. The central indigenous actor of current government discourse has been pushed aside. The Bolivian process presents a way of building a more equal state and a society that offers greater opportunities provided that these structural contradictions are resolved. Bolivia se funda como Estado Plurinacional, y como tal pretende desmontar el colonia-lismo interno que atraviesa el Estado y la sociedad. De esta manera reconoce la autodeterminación de los pueblos indígenas, las autonomías, la economía y justicia plural, la democracia comunitaria, y el suma qamaña (vivir bien). Por tanto plantea que el actor central de las transformaciones son los indígenas, y con esto constatamos que ni el sujeto obrero ni la clase media son actores centrales. Algunas de las contradicciones que se encuentran en su seno incluyen visiones de desarrollo que oscila entre el extractivismo y la conservación de la Madre Tierra y el vivir bien. El gobierno dice orientarse hacia el socialismo comunitario, pero el desarrollismo implicará la destrucción de los modos de sobrevivencia de la población nativa, indígena, consideradas ricas en cultura pero "arcaicas" desde la perspectiva occidental-industrialista. El actor central indígena que le da carne al discurso del gobierno ha sido arremetido. El proceso boliviano presenta la posibilidad de construir un Estado y una sociedad con mayores oportunidades e igualdad de condiciones, siempre y cuando resuelva estas contradicciones estructurales.